Geomorphological Study of the Karstic Polje in “Ein Alshams” “North Eastern of Safita” (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This research define and study geomorphological properties of the Karstic Polje, located in the southern parts of the coastal area “Beerat Aljerd and Ein alshams rgeons” For this issue, we have used “ G I S” Technology to clarify properties and place of this Polje through construction few of informatics slides that contain different types of data, showing Karstic Polje limits, dimensions, topography of the region, and situated Karstic characteristics Blind valleys, sink holes, solution doline, hums. Following, we have studied the Paleogeogeaphic development of the study area, in addition to the forming conditions, and Geomorphological periods related with this region. Finally, This study showed the great hydrology importance, resulted from presence of this Karstic Polje in the mentioned region, through infiltration of large quantities of rain water by precipitation with annual average up to 1475 m m. This water moves often through water bearing formations toward the west, where flow out of the Polje and contribute in consisting of water storage for the coastal area.